Stress coping strategies from islamic perspective among muslim teachers in islamic religious secondary school - Daud, Siti Rohana; Yaakob, Hafisah; Sehat, Nani Shuhada (2012)
Job stress is a major issue that is often associated with productivity and performance. Stress may be necessary for human survival, but the excess of it may lead to health and productivity problems. Many researches were conducted on stress and there are a lot of factors caused a job stress. Job stress faced by all of employees in the world includes Muslim employees. The presented data show that Asia has 69% of the world Muslim population while Africa has 27%. In addition, Muslims constitute 24% of the world population, or 1.65 billion people. Phenomena of Islam worker more expose on the load of jobs and may cause a job stress. Recently, studies on stress have focused on the Islamic view or perspective. It gives an idea of how stressful it happened and how it is managed based on Islamic Sharia. Many of researchers studied about coping strategies among Muslim employees. Therefore, the purposes of this study are to explore the stress issue from Islamic perspective. Research objectives are 1) To determine the level of stress among Muslim teachers. 2) To identify the stress coping strategies from Islamic perspective among the Muslim teachers. This study is descriptive and inference explanatory study which is using a quantitative approach through distribution of questionnaires. The sampling size for this research would be 70 Muslim teachers Islamic Religious secondary school at Pahang.